PENGARUH KUALITAS JASA PELAYANAN TERHADAP KEPUASAN PELANGGAN - Aryo Wibisono; Syahril Syahril (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2016)
PT. Indonesia Railways is an enterprise transportation service provider, where the modes of transportation are often used by consumers to travel long distances, and the price of transport service providers are not too different, then they (the companies) should be thinking how to grab share of existing market, so that the company will make profits. Therefore companies must compete on service providers to satisfy customers. Therefore there is need for research that is applied by using SEM methods (Structural Equation Modeling) in view of the customer and more towards the GAP analysis of the difference between reality and the difference is desired by consumers. With this then, can provide input to the company to consider the factors that correlate to customer satisfaction, so that the company's strategy in the form of customer satisfaction is more focused and effective. The results showed that the variables have a significant influence on complaint of customer satisfaction trains, and there was a GAP between reality and expectations of customers, so customers do not feel satisfied with the services already provided from these transport service. Keywords: Customer satisfaction, SEM (structural equation modeling), GAP Analysis.